Handwashing adherence during the COVID-19 pandemic: A longitudinal study based on protection motivation theory. (January 2023) - Szczuka, Zofia; Siwa, Maria; Abraham, Charles; Baban, Adriana; Brooks, Sydney; Cipolletta, Sabrina; Danso, Ebrima; Dombrowski, Stephan U.; Gan, Yiqun; Gaspar, Tania; Gaspar de Matos, Margarida; Griva, Konstadina; et al.
Abstract: Rationale: The associations between the number of COVID-19 cases/deaths and subsequent uptake of protective behaviors may reflect cognitive and behavioral responses to threat-relevant information. Objective: Applying protection motivation theory (PMT), this study explored whether the number of total COVID-19 cases/deaths and general anxiety were associated with cross-situational handwashing adherence and whether these associations were mediated by PMT-specific self-regulatory cognitions (threat appraisal: perceived vulnerability, perceived illness severity; coping appraisal: self-efficacy, response efficacy, response costs). Method: The study (#NCT04367337) was conducted in March–September 2020 among 1256 adults residing in 14 countries. Self-reports on baseline general anxiety levels, handwashing adherence across 12 situations, and PMT-related constructs were collected using an online survey at two points in time, four weeks apart. Values of COVID-19 cases and deaths were retrieved twice for each country (one week prior to the individual data collection). Results: Across countries and time, levels of adherence to handwashing guidelines were high. Path analysis indicated that smaller numbers of COVID-19 cases/deaths (Time 0; T0) were related to stronger self-efficacy (T1), which in turn was associated with higher handwashing adherence (T3). Lower general anxiety (T1) was related to better adherence (T3), with this effect mediated by higher response efficacy (T1, T3) and lower response cost (T3). However, higher general anxiety (T1) was related to better adherence via higher illness severity (T1, T3). General anxiety was unrelated to COVID-19 indicators. Conclusions: We found a complex pattern of associations between the numbers of COVID-19 cases/deaths, general anxiety, PMT variables, and handwashing adherence at the early stages of the pandemic. Higher general anxiety may enable threat appraisal (perceived illness severity), but it may hinder coping appraisal (response efficacy and response costs). The indicators of the trajectory of the pandemic (i.e., the smaller number of COVID-19 cases) may be indirectly associated with higher handwashing adherence via stronger self-efficacy. Highlights: The study investigates correlates of adherence to the CDC handwashing guidelines. Smaller number of COVID-19 cases/deaths were indirectly related to better adherence. Self-efficacy mediated associations between COVID-19 cases/deaths and handwashing. Higher general anxiety was indirectly related to better adherence via illness severity. Lower anxiety promoted better adherence via response costs and response efficacy.